Пошаговое объяснение:
Подстановкой:
3х + у = 1
-х + 2у = 11
у = 1 - 3х
-х + 2(1 - 3х) = 11
-х + 2 - 6х = 11
-х - 6х = 11 - 2
-7х = 9
х = -9/7
у = 1 - 3*(-9/7)
у = 1 + 27/7
у = 1 + 3. 6/7
х = -1. 2/7
у = 4. 6/7
ответ: (-1. 2/7; 4. 6/7)
Сложением:
2х + 3у = 12
2х + 3(1 - 3х) = 12
2х + 3 - 9х = 12
2х - 9х = 12 - 3
у = 1 - 3 * (-9/7)
Пошаговое объяснение:
Подстановкой:
3х + у = 1
-х + 2у = 11
у = 1 - 3х
-х + 2у = 11
у = 1 - 3х
-х + 2(1 - 3х) = 11
у = 1 - 3х
-х + 2 - 6х = 11
у = 1 - 3х
-х - 6х = 11 - 2
у = 1 - 3х
-7х = 9
у = 1 - 3х
х = -9/7
у = 1 - 3*(-9/7)
х = -9/7
у = 1 + 27/7
х = -9/7
у = 1 + 3. 6/7
х = -1. 2/7
у = 4. 6/7
х = -1. 2/7
ответ: (-1. 2/7; 4. 6/7)
Сложением:
3х + у = 1
-х + 2у = 11
2х + 3у = 12
3х + у = 1
2х + 3у = 12
у = 1 - 3х
2х + 3(1 - 3х) = 12
у = 1 - 3х
2х + 3 - 9х = 12
у = 1 - 3х
2х - 9х = 12 - 3
у = 1 - 3х
-7х = 9
у = 1 - 3х
х = -9/7
у = 1 - 3х
х = -9/7
у = 1 - 3 * (-9/7)
х = -9/7
у = 1 + 27/7
х = -9/7
у = 1 + 3. 6/7
х = -1. 2/7
у = 4. 6/7
ответ: (-1. 2/7; 4. 6/7)